Ocular Cicatricial Pemphigoid: Case Report - Revathi Rajaraman; Vaidee Vikram; Anita Raghavan (Delhi Journal of Ophthalmology)
Ocular Cicatricial Pemphigoid (OCP) is an autoimmune, progressive disorder that primarily affects the conjunctiva producing cicatrizing conjunctivitis and can progress to blindness. OCP can be a diagnostic and therapeutic challenge since it can present with different symptoms in different stages of the disease. We present 2 cases of OCP with such varying presentations, and highlight the need for early diagnosis and treatment with immunosuppressive agents to stabilize the ocular surface and prevent progression to blindness.